การประยุกต์เทคนิคโฟมแอสฟัลต์มาใช้ในการนำวัสดุชั้นทางเก่ากลับมาใช้งานใหม่ในประเทศไทย - วรภัทร เกตุนุติ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
Foamed asphalt is the result from the innovation process of developing asphalt cement application, where water is sprayed to mix with hot asphalt cement. This resulted in the rapid increase of the surface area of asphalt cement in a form of foam which reduces its viscosity, allowing a better mix with cold-damp aggregates. The purpose of this research is to study the feasibility and suitability of applying foamed asphalt to improve the quality of reclaimed asphalt pavement (RAP) or recycled materials in Thailand. The focus is on the feasibility of mixing aggregates from the RAP with new aggregates in different proportions ranging from 80:20, 50:50 and 0:100. It was found according to the result that the mixtures require foamed asphalt in different proportions of 2.1%, 2.6% and 3.4% by weight of aggregate respectively. Although the mixtures with higher percentage of aggregate from RAP exhibited lower indirect tensile strength, but its retained strength after soaking in water is comparatively high. It was found according to the resilient modulus test at different temperatures that the foamed asphalt mixture has lower temperature susceptibility than that of the hot-mix asphalt concrete. As regard to fatigue resistance and permanent deformation which are the indicators of performance in practical use, It was found that up to 50 percentage of aggregate from RAP can be used in the mix without any significant change to the fatigue resistance and the permanent deformation of the mix.